Boron Adsorption on Benchmark Soils of Punjab - Arora, Harsh; Bhardwaj, S.S.; Sharma, B.D. (Asian Journal of Chemistry, 2010)
The adsorption reactions of boron in soils strongly influence the release and fixation of applied boron and, thus, decide the efficiency of boron fertilization. Adsorption behaviour of B was investigated for six soil series of Punjab varying in physical and chemical characteristics. Results reveal that, in general, the adsorption of B increased with increase in concentration of boron and decreased with increase in temperature. Adsorption data for boron fitted well to the Freundlich isotherm and K values were positively correlated with clay and calcium carbonate content and negatively correlated with electrical conductivity and organic carbon content of the soil. Boron adsorption data also fitted well to the Langmuir equation. The values of distribution coefficient Kd, partial molar free energy (ΔG ) change and supply parameter were also calculated.